Australia's National Electricity Market: Optimising Policy to Facilitate Demand‐Side Response. (February 2016) - Nelson, Tim; Orton, Fiona
Abstract: In this article, we outline the recent reductions in electricity sector capital productivity and higher end use prices. Unsurprisingly, policy‐makers are now examining ways to encourage greater levels of consumer participation to improve capacity utilisation and outcomes for consumers. We find that consumers are likely to be better off by responding to retail, rather than wholesale generation, pricing. Retail prices reflect potential savings across all supply chain costs including the primary driver of recent price increases, capital‐intensive networks. Conversely, the wholesale electricity generation market is currently heavily oversupplied and savings for consumers are likely to be scarce.